Screening for sleep deprivation and mood states among staff nurses of tertiary care hospital in central India - Aryashree L; Verma, Prashant; Thakur, Aditya; Dhakar, Jagmohan Singh; Tiwari, Rajesh (Asian Journal of Medical Sciences, 2023)
Background: A Nurse’s fatigue raises significant concerns for individual and patient safety. The impact of sleep deprivation on the quality of patient care is an important consideration in today’s health-care environment. Aims and Objectives: The aim of this study was to find the proportion of sleep deprivation among nurses in a tertiary care hospital and to find the association between sleep deprivation and mood states among staff nurses. Materials and Methods: It was a cross-sectional design done in a duration of 2 months from September to October 2022. The study group consisted of nurses working in a tertiary care hospital located in Jabalpur district. A sample size of 70 nurses was calculated through the statistical formula. The questionnaire has three sections: Demographics (nine questions), Epworth sleep scale (eight questions), and Profile of mood states (65 questions). The collected data were tabulated and analyzed using MS Office Excel and SPSS version 21. Results: Interviews were conducted with 70 nurses and 8.6% of them were found to be excessively sleepy and should seek medical attention. Significant results have been obtained for the association with tension, depression, anger, fatigue, and confusion with sleep deprivation. Conclusion: The findings suggest that sleep deprivation exists in a considerable state. Some workplace interventions need to be done to make the efforts of nurses worthwhile and to increase their vigor and positive mood.